Aktivitas Antioksidan Produk Kopi dan Teh di Kota Samarinda: Antioxidant Activity of Coffee and Tea Products in Samarinda City - Aryanti Aryanti; Lizma Febrina; Nurul Annisa; Rolan Rusli (Jurnal Sains dan Kesehatan, 2021)
Free radicals can cause many problems on the body. Coffee and tea is a daily drink of many people and have antioxidant activity as an antidote to free radicals. The aim of this research was to compare the antioxidant activity of various coffee and tea products are circulating in Samarinda using DPPH method. The highest antioxidant activity of was SK3 coffee with 95.24%. The highest antioxidant activity was ST9 tea with 88.26%.